2017
DOI: 10.18535/jmscr/v5i7.160
|View full text |Cite
|
Sign up to set email alerts
|

Relative Assessment of Ketamine Nebulisation and Ketamine Gargle in Attenuating Post-Operative Sore Throat

Abstract: Sore throat is a utmost perceived morbidity following tracheal intubation in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…Ahuja et al .,[ 4 ] Aditya et al .,[ 14 ] Mehrotra et al .,[ 15 ] Kumar and Kumar,[ 16 ] and Jain and Kumar[ 17 ] studies showed reduced incidence and severity of POST with ketamine use by any route and the findings were consistent with our results.…”
Section: Discussionsupporting
confidence: 92%
“…Ahuja et al .,[ 4 ] Aditya et al .,[ 14 ] Mehrotra et al .,[ 15 ] Kumar and Kumar,[ 16 ] and Jain and Kumar[ 17 ] studies showed reduced incidence and severity of POST with ketamine use by any route and the findings were consistent with our results.…”
Section: Discussionsupporting
confidence: 92%